2008
DOI: 10.1093/ndt/gfn262
|View full text |Cite
|
Sign up to set email alerts
|

Induction of P450 1A by 3-methylcholanthrene protects mice from aristolochic acid-I-induced acute renal injury

Abstract: These results demonstrated that the induction of hepatic P450 1A1/2 protected against AAI-induced kidney injury through faster in vivo clearance of AAI and suggested an important role for hepatic P450s in the detoxification of AAI-induced renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
2
24
1
Order By: Relevance
“…Most importantly, in these studies AA induced either acute kidney failure or just mild changes in kidney fibrosis [25,27,28,29]. Most studies failed to show convincing images of kidney fibrosis [30,31,32]. Therefore, in this study, we aimed to develop a standardised protocol of kidney fibrosis in C57BL/6 mice using pure AAI, with extensive characterisation of tubulointerstitial fibrosis to demonstrate the relevance of the pathology to that in man.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, in these studies AA induced either acute kidney failure or just mild changes in kidney fibrosis [25,27,28,29]. Most studies failed to show convincing images of kidney fibrosis [30,31,32]. Therefore, in this study, we aimed to develop a standardised protocol of kidney fibrosis in C57BL/6 mice using pure AAI, with extensive characterisation of tubulointerstitial fibrosis to demonstrate the relevance of the pathology to that in man.…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro experiments using hepatic mouse microsomes show that CYP1A enzymes generate AAIa 47 . but the mouse model used to evaluate the role of CYP1A in the formation of AAIa in vivo by inducing CYP1A via 3-methycholanthrene (MC), produced ambiguous results 47,52 , MC induces other enzymes beside CYP1A. Although treatment of mice with MC leads to decrease in AAI concentrations in the liver and kidney, no increase in AAIa concentrations was found in the liver, only in the kidney of mice treated with the higher dose of AAI (20 mg/kg body weight).…”
Section: The Role Of Biotransformation Enzymes In the Development Of mentioning
confidence: 99%
“…Taking into account all the currently known data, we propose that the pathways of AAI metabolism are determined by: the binding affinity of AAI to CYP1A or NQO1 enzymes and their enzymatic turnover, as well as the balance between the efficiency of CYP1A in oxidizing and reducing AAI. To test this assumption and to complement earlier studies 25,45,47,52,54 , we are currently investigating the formation of AAI-DNA adducts in HRN and CYP1A gene knock-out mouse models.…”
Section: The Role Of Biotransformation Enzymes In the Development Of mentioning
confidence: 99%
“…The pharmacokinetics of AAI in rodents Chen et al, 2008;Xue et al, 2008;Liu et al, 2009;Yue et al, 2009), and a few in herbivore, such as rabbits, have been reported (Chen et al, 2007). Chronic renal injuries, such as tubulointerstitial fibrosis and tumors, are induced by AAI in rodent.…”
Section: Introductionmentioning
confidence: 99%